Seismicity in Costa Rica during 2013 - Linkimer, Lepolt (2014)
During 2013, the National Seismological Network (RSN: UCR-ICE) located 2547 earthquakes and reported 261 felt events. There were seven significant earthquakes with magnitude ≥ 5,0. The majority (85%) of earthquakes were shallow (< 30 km) and 56% had a low magnitude (Mw 3,0-3,9). Local and regional faulting caused 52% of the felt earthquakes and 45% occurred due to the subduction of the Cocos Plate beneath the Caribbean Plate and the Panama microplate. The highest intensity observed during 2013 was VI (Modified Mercalli, MM) in the Sixaola region (Limon) during the May 27 earthquake (5.6 Mw) with epicenter in western Panama